PENGARUH ASSET TANGIBILITY, SALES GROWTH, DAN BUSINESS RISK TERHADAP STRUKTUR MODAL (STUDI KASUS PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023) - Rani Nopita; Miftahol Horri (Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the effect of Asset Tangibility, Sales Growth, and Business Risk on Capital Structure in energy sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The research method used is quantitative analysis with multiple linear regression tests using SPSS version 26. The results showed that simultaneously Asset Tangibility, Sales Growth, and Business Risk affect Capital Structure. Partially, Asset Tangibility has a positive and significant effect on Capital Structure. High fixed assets can be a guarantee that makes it easier for companies to obtain funding from investors and creditors. Sales Growth variable has a positive and significant effect on Capital Structure. The increase in sales can increase cash which can be a source of internal capital for the company. Business risk variable negatively and significantly influences Capital Structure. This indicates that companies with high business risk tend to reduce debt